EFFECT OF ZEOLITE ON HEAVY METALS AND DISSOLVED CHEMICAL SUBSTANCES IN THE WATER: CASE STUDY OF STUDENT NEIGHBORHOOD AREA IN DARMAGA, WEST JAVA - Dwita Siallagan; Suwardi Suwardi (Institut Teknologi Bandung, 2003)
Bad sanitation environment on student neighborhood area causes the decreasing of ground water quality, whereas the ground water is the main water source of that area. Physical, chemical, and biological parameters showed that the ground water which consumed are contaminated by organic matters from safety tank, ground particles and heavy metal (Fe and Mn). Fe and Mn rates on the well water are 0,0066-0,1657 mg/l dan 0,035-0,072 mg/l. While Fe and Mn ratea on waste water are 0,2193-0,7102 mg/l dan 1,90-4,70 mg/l. Dissolve solid suspention rate on the ground water and domestic waste water are 0,0066-0,1657 mg/l dan 0,035-0,072 mg/l respectively. Chemically, it was below the permitted limit 0,3 mg/l and 0,1 mg/l, but physically the ground water looks coloured, tested and smell. These may be caused by littering and too crowded neighborhood and organic matter intrusion to the well. One of the alternative to decrease the metal rate and dissolve solid suspention on water ground is using zeolite. Ground water analysis showed that zeolite can decreases the Fe and Mn rates from 0,92 ppm to 0,07 ppm and from 0,34 ppm to 0,048 ppm (around 85-90 %).